PENGATURAN MENGENAI PERJANJIAN NOMINEE DAN KEABSAHANNYA (DITINJAU DARI KITAB UNDANG-UNDANG HUKUM PERDATA DAN UNDANG-UNDANG NOMOR 5 TAHUN 1960 TENTANG PERATURAN DASAR POKOK-POKOK AGRARIA) - Widhi Wiratama, Gde; Rai Djaja, Ida Bagus (Kertha Semaya : Journal Ilmu Hukum; Vol. 01, No. 04, Mei 2013)
Indonesian agrarian law is not allowed the citizens who marriage with the foreigner and not making the marriage treaty or the foreigner. The condition makes the parties who have the importance to look for the way to solve the problems. The way used to solve the problem is with doing the treaties nominee between the citizens and foreigners, which is used the name of another parties (Indonesian citizen) that apointed as nominee for the ground owner license.
Keywords: Agrarian Law, Right For The Ground Owner, Nominee Treaty, Foreigner